ANTIBACTERIAL ACTIVITY TEST OF ETHANOL EXTRACT OF TEMBELEKAN LEAVES (Lantana Camara L) AGAINST BACTERIA THAT CAUSE SKIN INFECTIONS USING AGAR DIFFUSION METHODS AND TLC-BIOAUTOGRAPHY - Sulfiana, Sulfiana (Fakultas Farmasi, Universitas Muslim Indonesia, 2023)
Tembelekan with the scientific name Lantana camara Linn which is used for generations in medicine that utilizes leaves to treat skin diseases such as tinea versicolor, ringworm and ringworm. Skin infection is a disease that attacks the surface of the body, and is caused by various causes such as bacteria, viruses, and fungi. In this study, the antibacterial activity of the ethanolic extract of the tembelekan leaf (Lantana camara L) was tested using the agar diffusion method and TLC- Bioautography against several test bacteria including Propionibacterium acnes, Pseudomonas aeruginosa, Staphylococcus aureus, Staphylococcus epidermidis. The results of the screening test for ethanol extract of tembelekan leaves (Lantana camara L) at a concentration of 0.5% can inhibit and kill the growth of the test bacteria. Then proceed with testing the antibacterial activity using the agar diffusion method. The result is that the diameter of the largest inhibition zone of the ethanolic extract of tembelekan leaf (Lantana camara L) was obtained at a concentration of 8%, namely Propionibacterium acnes (15.57 mm), Pseudomonas aeruginosa (17.82 mm), Staphylococcus aureus (16.14 mm). , Staphylococcus epidermidis (15.2 mm). The TLC results of the ethanolic extract of tembelekan (Lantana camara L) leaves with eluent n hexane: ethyl acetate (7: 4) viewed under UV light at 254 nm and 366 nm, 6 stains were seen, each with an Rf value of Rf1 0.90. , Rf2 0.8, Rf3 0.67, Rf4 0.6, Rf5 0.43, Rf6 0.25. Furthermore, the results of TLC-Bioautography showed that there were 2 spots that were active in inhibiting all test bacteria with Rf values = 0.8 and 0.25, respectively.